Família de idosos institucionalizados: perspectivas de trabalhadores de uma instituição de longa permanência - Santos, Naiana Oliveira dos (2013)
Institutions of Long Term for Elderly are places of residencial features, aiming the collective household of people equal or over 60 years, who seek protection and support that, frequently, are not available in their family and social environment. Thus, when the elderly come to live in these institutions there is a trend that they move away from their original families, changing habits and, consequently, the risk of isolation and dissatisfaction with life. The aim of this study is: to analyze the perspectives of workers at a nursing home on the families of institutionalized elderly; and the specific objectives are: to know the workers persception of a nursing home on the family of institutionalized elderly; understand how the workers notice the participation and the role of family life in the context of institutionalized elderly; and describe how workers perceive the role of the institution in relation to the institutionalized elderly. The research was qualitative, exploratory, where 16 workers of a multidisciplinary team working in a nursing home for elderly were interviewed. The data collection happened from February to June, 2012. The data was subjected to thematic analysis which converged in the preparing of three articles: Coexist is necessary: the Family as reference of institutionalized elderly , which presentes how workers perceive the families of seniors in nursing home. The workers notice that the family does not visit the institution, and it considers the celebration dates as the main occasions in which the family takes part in. They understand that the consanguineal family abandons their elderly and nobody takes its place. The second article is Participation and role of the family in the context of institutionalized elderly: the perspective of workers , presenting the different ways in which the elderly families get involved. The workers consider that the main role of family is the permanent responsability with its elderly, even after the institutionalization. The third article os The institution for seniors as a space to build a new family , pointing out that the role of nursing homes in relation to their elderly creates the possibility of constituting a new family within the institution. This relation also leads to a overload of being a family , because of the demands for care in the institution raise among the workers and the elderly. The study results help to pond about the workers in an elderly nursing home perspective on the elderly s families. When the family is presente the elderly are better in terms of health, adaptation and participation in the activities proposed by the workers. So the workers visualize the Family as a care system for the seniors, considering that coexisting may be a form of developing and maintaining an affective balance between elderly and their families. Regarding this, the different forms of participation for the family and the coexistence with the elderly in the nursing home contribute for the sênior, where they presente better health conditions and better life quality. Besides that, it is considered that the findings in this study may help to support actions of caring with old institutionalized people and their families.